Sosialisasi Pembuatan Pupuk Trichokompos Dengan Memanfaatkan Limbah Pertanian di Desa Sidodadi, Kecamatan Tempurejo, Kabupaten Jember - Eliyatiningsih Eliyatiningsih; Rindha Rentina Darah Pertami; Hanif Fatur Rohman; Edi Siswadi; M. Zayin Sukri (Indonesian Journal Publisher, 2022)
Sidodadi village, Tempurejo sub-district is one of the villages in the southern part of Jember Regency. The majority of the population works in the agricultural sector. The village is known as an agriculture-based village in Jember Regency. The “Ngudi Rejeki” Farmer's Group in Sidodadi Village, Tempurejo District, Jember is constrained by the problem of increasing non-subsidized fertilizer prices which makes it an obstacle in increasing agricultural yields. On the other hand, the regulation of subsidized fertilizers is quite limited among farmers so that it is suspected that it will increase production costs. The results of direct discussions with partners revealed an interesting fact that the average use of chemical fertilizers is very high even though currently the use of organic fertilizers can reduce production costs with the basic ingredients for making fertilizers derived from agricultural production residues. This area has a lot of waste rice straw and cow dung that has not been utilized. Some of the solutions offered to deal with partner problems include socializing the use of organic fertilizers, one of which is trichocompost fertilizer as a substitute for the use of chemical fertilizers, demonstrations on how to make trichocompost fertilizer with cow dung as raw material with the biodecomposer Trichoderma sp. This extension activity is carried out with a participatory approach, which means that farmers as extension participants are actively involved in the activity. The method used in the implementation of community service is socialization, discussion, and demonstration of making trichocompost fertilizer. The results of the socialization of trichocompost organic fertilizer obtained as many as 77% of farmers interested in using trichocompost fertilizer as soil improvement fertilizer.